1997
DOI: 10.1074/jbc.272.38.23565
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transactivation by Two Isoforms of the Orphan Nuclear Hormone Receptor CAR

Abstract: We have identified a new murine orphan member of the nuclear hormone receptor superfamily, termed mCAR, that is closely related to the previously described human orphan MB67, referred to here as hCAR. Like hCAR, mCAR expression is highest in liver. In addition to the most abundant mCAR1 isoform, the mCAR gene expresses a truncated mCAR2 variant that is missing the C-terminal portion of the ligand binding/dimerization domain. The mCAR gene has 8 introns, and this mCAR2 variant is generated by a splicing event t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
194
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(209 citation statements)
references
References 50 publications
13
194
1
1
Order By: Relevance
“…The strongest evidence for this hypothesis is the loss in inhibition of ER action by CAR if the C-terminal 8 amino acids of CAR are deleted. This mutant retains the ability to bind to DNA (25) and is FIG. 8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strongest evidence for this hypothesis is the loss in inhibition of ER action by CAR if the C-terminal 8 amino acids of CAR are deleted. This mutant retains the ability to bind to DNA (25) and is FIG. 8.…”
Section: Discussionmentioning
confidence: 99%
“…this mutant CAR heterodimerized with RXR and bound to the CAR/RXR binding site; however, transcriptional ability was completely abolished (25). This mutant CAR has also been reported to be expressed at levels similar to wild type (25).…”
Section: Fig 5 Car/rxr Can Bind To the Ere But Car In 100-fold Excmentioning
confidence: 99%
See 1 more Smart Citation
“…CAR is unusual among nuclear receptors in having a high constitutive activity when assayed in cultured cells (5). The initial ligands identified for CAR were androstanes that were reverse agonists and down-regulated CAR activity (6).…”
mentioning
confidence: 99%
“…Similar to PXR (also known as steroid and xenobiotic receptor SXR), CAR heterodimerizes with RXR and binds to the phenobarbital responsive enhancer module (PBREM) to induce the transcription of CYP2B genes (Baes et al 1994;Choi et al 1997;Honkakoski and Negishi 1997). Closer examination of the PBREM and the other CARregulated promoters revealed that CAR preferentially binds to DR4 (direct repeat spaced by 4 nucleotides) binding sites (Honkakoski et al 1998).…”
Section: Nuclear Receptors Car and Pxrmentioning
confidence: 99%